Use of p38 MAPK Inhibitors for the Treatment of Werner Syndrome - Mark C. Bagley; Terence Davis; Paola G. S. Murziani; Caroline S. Widdowson; David Kipling (MDPI AG, 2010)
Werner syndrome provides a convincing model for aspects of the normal ageing phenotype and may provide a suitable model for therapeutic interventions designed to combat the ageing process. Cultured primary fibroblast cells from Werner syndrome patients provide a powerful model system to study the link between replicative senescence in vitro and in vivo pathophysiology. Genome instability, together with an increased pro-oxidant state, and frequent replication fork stalling, all provide plausible triggers for intracellular stress in Werner syndrome cells, and implicates p38 MAPK signaling in their shortened replicative lifespan. A number of different p38 MAPK inhibitor chemotypes have been prepared rapidly and efficiently using microwave heating techniques for biological study in Werner syndrome cells, including SB203580, VX-745, RO3201195, UR-13756 and BIRB 796, and their selectivity and potency evaluated in this cellular context. Werner syndrome fibroblasts treated with a p38 MAPK inhibitor reveal an unexpected reversal of the accelerated ageing phenotype. Thus the study of p38 inhibition and its effect upon Werner pathophysiology is likely to provide new revelations into the biological mechanisms operating in cellular senescence and human ageing in the future.